Diet–tissue discrimination factors (δ15N and δ13C values) for blood components in Magellanic (Spheniscus magellanicus) and southern rockhopper (Eudyptes chrysocome) penguins. (7th February 2020) - Jenkins, Edward; Gulka, Julia; Yurkowski, David J.; Davoren, Gail K.; Gonzalez, Lana
Abstract : Rationale: Analysis of the stable isotope ratios of carbon and nitrogen ( δ 13 C and δ 15 N values) is increasingly being used to gain insight into predator trophic ecology, which requires accurate diet–tissue discrimination factors (DTDFs), or the isotopic difference between prey and predator. Accurate DTDFs must be calculated from predators consuming an isotopically constant diet over time in controlled feeding experiments, but these studies have received little attention to date, especially among seabird species. Methods: In this study, aquarium‐housed Magellanic ( Spheniscus magellanicus ) and southern rockhopper ( Eudyptes chrysocome ) penguins were fed a single‐prey source diet (capelin Mallotus villosus ) for eight weeks. Stable isotope ratios ( δ 13 C and δ 15 N values) of penguin blood (cellular component and plasma) and capelin were measured using mass spectrometry and then used to calculate DTDFs for both components of penguin blood by comparison with prey values. Results: The DTDFs for plasma were −0.63 ± 0.49 (mean ± SD) and −0.27 ± 0.22 for δ 13 C values, and 2.60 ± 0.50 and 2.78 ± 0.22 for δ 15 N values for Magellanic and southern rockhopper penguins, respectively, while the DTDFs for the cellular component were 1.22 ± 0.03 and 1.26 ± 0.03 for δ 13 C values, and 2.54 ± 0.07 and 2.43 ± 0.17 for δ 15 N values. Conclusions: We compare our DTDFs with published values from blood components of penguins and discuss the effects that lipid extraction, sample storage, and diet have on the DTDFs of penguin blood components. This study provides accurate DTDFs of blood components for two seabird species of conservation concern, and is one of the first to provide plasma DTDFs for penguins, which are underrepresented in the seabird literature.